TINJAUAN HUKUM EKONOMI SYARIAH TERHADAP JUAL BELI IKAN DENGAN PENANGGUHAN PEMBAYARAN (Studi Kasus di Ma’had Al-Zaytun) - Raihan Aflah Zakiyuddin; Rizal Maulana; Irvan Iswandi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to analyze the practice of fish trading with deferred payment between the Kitchen and the Fish Slaughterhouse at Ma’had Al-Zaytun from the perspective of Islamic economic law. The practice is carried out routinely without a written contract, relying solely on mutual trust and transaction notes. Using a qualitative method through field research and literature review, data were collected via observation, interviews, and documentation. The results show that the transaction meets the daily consumption needs of students, with payments made within a maximum period of one month. From the perspective of Islamic economic law, this practice falls under the category of bai’bi tsaman ajil, fulfills the legal requirements of a valid contract, ensures transparency, and does not contain elements of riba, thus it is considered permissible. Keywords: fish trading, deferred payment, Islamic economic law